Hybrid Procedural Management of Multiple Pulmonary Arteriovenous Malformations In A Patient With Hereditary Hemorrhagic Telangiectasia: A Case Report - Sanubari, Aulia Agung; Budiono, Enrico A.; Prasetyo, Arif (Jurnal Locus Penelitian dan Pengabdian, 2024)
Hereditary Hemorrhagic Telangiectasia (HHT) is an autosomal dominant disorder characterized by vascular malformations, including Pulmonary Arteriovenous Malformations (PAVMs), which can lead to serious complications such as dyspnea and hemorrhage. This report features a 37-year-old woman with HHT and multiple PAVMs. The diagnosis was established through physical examination, laboratory tests, and thoracic multislice computed tomography (MSCT). A hybrid management approach was applied, including embolization and thoracotomy. The patient underwent successful embolization of the inferior segment, followed by thoracotomy to overcome procedural difficulties. After the intervention, the patient's symptoms improved significantly, with no recurrence. Management of complex PAVMs may require a combination of methods, including embolization and surgery. The importance of early detection and adaptive management in HHT patients is expressed, given the high risk of complications. Embolization is the primary treatment for PAVMs, but in complex cases, surgical intervention is required. This study emphasizes the importance of a hybrid management approach and early detection in preventing serious complications in HHT patients, as well as the need for the development of better clinical guidelines for the management of PAVMs.